Microsatellites from the burbot (Lota lota), a freshwater gadoid fish (Teleostei) - Sanetra, Matthias; Meyer, Axel (My University, 2005)
We developed 21 polymorphic dinucleotide microsatellite loci, (CA)n and (CT)n, for the Holarctic freshwater fish, Lota lota, using an enriched genomic library protocol. The species has an interesting life history because winter-spawning adults migrate over long distances to form spawning aggregations, a behaviour which should maintain genetic homogeneity across large spatial scales. Availability of the reported microsatellites will facilitate the investigation of population genetic structure with regard to postglacial colonization history and conservation strategies. The primers were screened on 30 individuals from a natural population (Lake Constance, southern Germany), revealing three to 24 alleles per locus with expected heterozygosities ranging from 0.48 to 0.93.
Keywords: burbot; Lake Constance; Lota lota; microsatellites; population genetics; 570